Options for Combination Therapy in Type 2 Diabetes: Comparison of the ADA/EASD Position Statement and AACE/ACE Algorithm - Bailey, Timothy (The American journal of medicine, 2013)
Treating patients with diabetes is one of the most challenging and important activities a physician (primary care physician or specialist) can undertake. A key to successful therapy for type 2 diabetes is the insight that this condition is progressive and that the need for additional agents over time is normative. The ability to individualize therapy by patient and medication characteristics comes from experience and knowledge of pertinent clinical studies. However, guidelines from expert bodies such as the American Diabetes Association/European Association for the Study of Diabetes and American Association of Clinical Endocrinologists/American College of Endocrinology can help clinicians of all levels of expertise to approach therapy choices more rationally. There is unity across these guidelines about the role and benefits of metformin as first-line pharmacological treatment, probability of good efficacy, low risk of hypoglycemia, modest weight loss, and overall long-term data. Unfortunately, this unity does not extend to recommendations for subsequent pharmacological agents and their use in combination to intensify treatment when insulin is not (yet) appropriate. Across both statements, some drug classes seem more prominent, and looking at their benefit–risk profile, it is clear why this is the case. The most profound recent change in diabetes therapy has been the introduction of incretin therapies. Incretin therapies minimize 2 important adverse effects seen with many other therapies: hypoglycemia and weight gain. These agents have increased the range of options available for early intensification of treatment of type 2 diabetes. In combination with more established therapies, there are more opportunities than ever to accommodate patient preferences while improving glycemic control and harnessing extraglycemic benefits of a second (or third) agent.